Description of students' mathematical concept understanding ability, in terms of initial mathematical ability. Issue 4 (June 2021) - Agustina, L; Zaenuri,; Wardono,
Abstract: The purpose of this study was to determine the description of students' ability to understand mathematical concepts in the basic introductory course of mathematics in terms of their initial mathematical abilities. This research is a qualitative research. The subjects in this study were students of the Mathematics Education Study Program who took an Introduction to Basic Mathematics at Indraprasta University PGRI Jakarta. The sampling technique used was purposive sampling, while the instruments used were documents (test results of students' initial mathematical abilities and understanding of mathematical concepts), observation sheets, interview guides, and researchers. The research data were collected using triangulation techniques. The results of this study were that the students' initial mathematical abilities were good enough, but the indicators of student functional understanding were still a little difficult.